The decline of tourist destinations: an evolutionary perspective on overtourism - Benner, Maximilian (Sustainability, 2020)
The term overtourism has generated considerable attention both in academic discourse and public debate. The actual or perceived impact of overtourism on destinations has significant ecological, social, and cultural consequences. However, a crucial question remains unanswered: What does overtourism do to a destination’s tourism industry itself? At the core of this question is whether overtourism is a self-limiting phenomenon or a cumulative one, and how precisely overtourism shapes patterns of quantitative or qualitative decline of a destination’s tourism sector. This article offers a conceptual discussion of the impact of overtourism on a destination’s local tourism sector by refining the latter stages of Butler’s tourist area lifecycle through forms of path decline known from evolutionary economic geography. By combining these two theorical approaches and refining the typology of path decline from evolutionary economic geography to the case of tourism under an overtourism scenario, this article suggests that, in the absence of exogenous changes due to policy interventions or public pressure, under an overtourism scenario, a destination’s tourism sector might contract, downgrade, dislocate, and eventually even disappear. Further research should focus on how to prevent these forms of path decline.